Product Features and Customers Satisfaction of Patanjali Product: Evidence From Kathmandu, Nepal - Ballav Niroula; Achyut Gyawali (Jambura Science of Management, 2022)
The objectives of this study are to identify the features of Patanjali products and it focuses to identify the satisfaction level and purchasing decision of consumer by the features of Patanjali products. In this research, convenient sampling technique were used to get the sample, correlation and regression were used in order to get the result. Descriptive statistics is used to explain the respondents’ perception towards the features of Patanjali product. In this study, the data was collected through questionnaire from 300 respondents. This research used SPSS - 23 for analysis. This study has been done on four attributes or determinants of Patanjali product, they are price, quality, availability and healthy (organic) of product. The result of this study indicates that there is positive relationship between the features of Patanjali product and satisfaction. It can be said that the independents variables have effect on consumer satisfaction of Patanjali products. The producer and marketing managers are recommended to focus on the product features in order to obtain loyal satisfied customers.